The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00198-009-0920-3
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality following hip fracture: a systematic epidemiological review

Abstract: This systematic literature review has shown that patients experiencing hip fracture after low-impact trauma are at considerable excess risk for death compared with nonhip fracture/community control populations. The increased mortality risk may persist for several years thereafter, highlighting the need for interventions to reduce this risk.Patients experiencing hip fracture after low-impact trauma are at considerable risk for subsequent osteoporotic fractures and premature death. We conducted a systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
572
2
30

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 862 publications
(663 citation statements)
references
References 100 publications
35
572
2
30
Order By: Relevance
“…In addition, many (71%) were unable to live in conditions similar to those before the (77) These outcomes are similar to long-term outcomes for people with femoral neck fractures. (78)(79)(80)(81) A comprehensive review of 6409 femoral shaft fractures in Swedish inpatients showed a bimodal age distribution of incidence in both males and females, (82) similar to that reported by Singer and colleagues. (83) The age-specific incidence rates (per 100,000) for subtrochanteric fractures increased between the 65-and 85-year categories in both males and females in Iran, (84) in the United States, (85) and in the United Kingdom.…”
Section: Epidemiology Of Subtrochanteric and Femoral Shaft Fracturessupporting
confidence: 71%
“…In addition, many (71%) were unable to live in conditions similar to those before the (77) These outcomes are similar to long-term outcomes for people with femoral neck fractures. (78)(79)(80)(81) A comprehensive review of 6409 femoral shaft fractures in Swedish inpatients showed a bimodal age distribution of incidence in both males and females, (82) similar to that reported by Singer and colleagues. (83) The age-specific incidence rates (per 100,000) for subtrochanteric fractures increased between the 65-and 85-year categories in both males and females in Iran, (84) in the United States, (85) and in the United Kingdom.…”
Section: Epidemiology Of Subtrochanteric and Femoral Shaft Fracturessupporting
confidence: 71%
“…1,4,14,17 But, at the mean follow-up for 2.12 years showed 50% mortality in extremely old population, which is higher than elderly population reported in literature. 1,16,17 Females have higher risk of a hip fracture, 11 but males have higher mortality rates than females with a hip fracture. 24 In our study, extremely old patients showed no differences mortality rates between males and females (p ¼ 0.11).…”
Section: Discussionmentioning
confidence: 99%
“…This increased mortality in hip fracture patients has been documented in the first year after fracture and remains high in the subsequent years of followup. 16,17 The purpose of this study is report a less seen age-group of hip fracture patients and to investigate mortality, walking ability, functional status changes after surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In such individuals, an acute episode of disuse atrophy (e.g. a hip fracture) can lead to disability in terms of mobility, increased hospitalization, and loss of independence, which can culminate in premature mortality 11, 12. Hence, the timely recovery of muscle mass and strength is the key goal for the physical rehabilitation of patients with disuse atrophy.…”
Section: Introductionmentioning
confidence: 99%